Optimizing Environmental Governance Towards a HIBRIDA Barru: A Collaborative Governance Approach to Sustainable Development - A. Pananrangi, M (SEAN Institute, 2026)
Environmental governance has become a strategic issue in achieving sustainable development, particularly in regions facing increasing environmental challenges and demands for inclusive governance. The concept of a HIBRIDA Barru emphasizes the integration of environmental sustainability, technological innovation, and community participation as a foundation for regional development. This study aims to analyze the optimization of environmental governance towards the realization of a HIBRIDA Barru through a collaborative governance approach. A qualitative descriptive method was employed to explore the roles and interactions of key stakeholders, including local government agencies, community organizations, the private sector, and environmental groups. Data were collected through in-depth interviews, observations, and document analysis and were analyzed using data reduction, data display, and conclusion-drawing techniques. The findings reveal that collaborative governance has played a significant role in strengthening environmental management by fostering stakeholder participation, enhancing coordination mechanisms, and promoting shared responsibility in environmental protection efforts. Furthermore, the integration of digital technologies and community-based environmental initiatives has improved environmental monitoring, resource management, and public awareness. However, challenges remain, including limited institutional capacity, resource constraints, and varying levels of stakeholder commitment. The study concludes that optimizing environmental governance through collaborative governance provides an effective framework for achieving sustainable development and advancing the HIBRIDA Barru vision. Strengthening cross-sector collaboration, improving digital infrastructure, and enhancing community engagement are essential for ensuring long-term environmental sustainability and regional resilience.